The heat-labile enterotoxin B subunit bio-adjuvant linked to Newcastle disease virus recombinant hemagglutinin neuraminidase elicited a humoral immune response in animal model: The LTB linked to HN elicited a humoral immune response against NDV - Rahmani, Mehregan; Mozafari, Atena; Jafari, Mahyat; Salmanian, Ali Hatef (Cellular and Molecular Biology, 2023)
Newcastle disease is a highly contagious viral infection primarily affecting poultry, leading to significant economic losses worldwide due to its high morbidity and mortality rates. Given the severity of the disease and its impact on the poultry industry, there is an urgent need for a preventative approach to tackle this issue. Developing an efficient and effective vaccine is a valuable step toward reducing the burden of this virus. Consequently, investing in preventive measures, such as vaccination programs, is a top priority to mitigate the economic losses associated with Newcastle disease and protect the livelihoods of those relying on the poultry industry. Despite many vaccines against this viral disease, it still infects many wild and domestic birds worldwide. In this work, chimeric proteins, composed of the recombinant B subunit of Enterotoxigenic E. coli with one or two HN (Hemagglutinin-neuraminidase) subunits of NDV (LHN and LHN2, respectively), expressed using E.coli host. In-silico, in-vitro, and In-vivo procedures were performed to evaluate the immunogenicity of these proteins. The sera from immunized mice were analyzed using Western Blotting and ELISA. The LHN2 protein with an extra HN subunit elicited a higher antibody titer than the LHN protein (P<0.05). Both products could effectively elicit an immune response against NDV and can be considered a component of Newcastle disease vaccine candidates.